Identifying factor productivity from micro-data: The case of EU agriculture - Martin Petrick; Mathias Kloss (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2018)
We examine the plausibility of four established and innovative identification strategies for agricultural production functions using farm-level panel datasets from five EU countries. Newly suggested proxy and dynamic panel approaches provide attractive conceptual improvements over received Within and duality models. Even so, empirical implementation of such advancements does not always live up to expectations. This is particularly true for the dynamic panel estimator, which mostly failed to identify reasonable elasticities for the (quasi-) fixed factors. Less demanding proxy approaches represent an interesting alternative for agricultural applications. In our EU sample, high production elasticities for materials prevail. Hence, improving the availability of working capital is the most promising way to increase agricultural productivity. – – Auf der Grundlage von einzelbetrieblichen Paneldatensätzen aus fünf EU Ländern untersuchen wir die Plausibilität von vier etablierten und innovativen Identifikationsstrategien für landwirtschaftliche Produktionsfunktionen. Die in jüngerer Zeit vorgeschlagenen Proxy- und dynamischen Panel-Ansätze bieten aussichtsreiche konzeptionelle Verbesserungen gegenüber herkömmlichen "Within" und Dualitätsmodellen. Die empirische Umsetzung dieser Weiterentwicklungen erfüllt jedoch nicht immer die Erwartungen. Dies trifft besonders auf den dynamischen Panel-Schätzer zu, dem es überwiegend nicht gelang, glaubwürdige Elastizitäten für die (quasi-) fixen Faktoren zu identifizieren. Weniger anspruchsvolle Proxy-Ansätze stellen eine interessante Alternative für landwirtschaftliche Anwendungen dar. In unserer EU Stichprobe fanden wir überwiegend hohe Produktionselastizitäten für Betriebsmittel. Die Verbesserung der Verfügbarkeit von Betriebsmittelkrediten erscheint daher als vielversprechender Weg, um die landwirtschaftliche Produktivität zu erhöhen.
urn:nbn:de:gbv:3:2-90157
Keywords: C13; C23; D24; Q12; 330; agricultural factor productivity; production function estimation; EU; Farm Accountancy Data Network; Landwirtschaftliche Faktorproduktivität; Schätzung von Produktionsfunktionen; Testbetriebsnetz